Fishing Gears in Sarawak: A Preliminary Survey - Maidin Mohd Samsul Rohizad; Harun Nadiayatul Atikah; Mustapha Mastura; Abdul Wahab Abdullah; Norhanida Daud; Jamil Musel (E3S Web of Conferences)
Unique to Sarawak, the fishing gears double-rig trawl, paka, panau, and rantau were gears that could only be found here. The focus of the present study was to catalog the diversity of fishing equipment across two regions, Wilayah II (Belawai, Daro, Mukah, Sarikei, Sibu and Tg Manis) and Wilayah III (Bintulu, Lawas, Limbang and Miri), via the interview method. A total of 163 respondents participated in the survey. In Wilayah II, 12 distinct types of fishing gears were identified, with monofilament gill nets (43.90%), fish trawl nets (30.49%), rentang (4.88%), bottom longlines (3.66%), and nylon gill nets (3.66%) being the most prevalent. Less common gears included paka, panau, shrimp trawl nets, rentang for jellyfish, modern bubu, and rantau. In Wilayah III, 14 different types of fishing gears were recorded, with monofilament gill nets (46.91%) and three-layer shrimp nets (20.99%) being predominant, followed by fish trawl nets (6.17%) and shrimp trawl nets (6.17%). Other less dominant gears included were modern bubu, panau, rantau, nylon gill nets, and bottom longlines. The mesh sizes of monofilament gill nets in both regions ranged from 25 to 170 mm, adhering to the regulations and guidelines set by the Department of Fisheries, Malaysia.